Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Selena and Drake are evaluating the expression [tex]\left(\frac{r s^{-2}}{r^2 s^{-3}}\right)^{-1}[/tex], when [tex]r=-1[/tex] and [tex]s=-2[/tex].

Selena's Work:
[tex]\[
\left(\frac{r s^{-2}}{r^2 s^{-3}}\right)^{-1} = \left(r^{-1} s\right)^{-1} = \frac{r}{s}
\][/tex]
[tex]\[
\left(\frac{(-1)(-2)^{-2}}{(-1)^2(-2)^{-3}}\right)^{-1} = \left(\frac{(-1)(-2)^3}{(-1)^2(-2)^2}\right)^{-1}
\][/tex]
[tex]\[
= \frac{-1}{-2} = \frac{1}{2}
\][/tex]

Drake's Work:
[tex]\[
\left(\frac{r s^{-2}}{r^2 s^{-3}}\right)^{-1}
\][/tex]
[tex]\[
\left(\frac{(-1)(-2)^{-2}}{(-1)^2(-2)^{-3}}\right)^{-1} = \left(\frac{(-1)(-2)^3}{(-1)^2(-2)^2}\right)^{-1}
\][/tex]
[tex]\[
= \left(\frac{-8}{4}\right)^{-1} = \frac{4}{-8} = -\frac{1}{2}
\][/tex]

Who is correct and why?


Sagot :

Let's evaluate the expression [tex]\(\left(\frac{r s^{-2}}{r^2 s^{-3}}\right)^{-1}\)[/tex] when [tex]\(r = -1\)[/tex] and [tex]\(s = -2\)[/tex] by examining the steps given by Selena and Drake.

Selena's Work:
1. Expression: [tex]\(\left(\frac{r s^{-2}}{r^2 s^{-3}}\right)^{-1}\)[/tex]
2. Simplify the expression inside the parentheses:
[tex]\[ \frac{r s^{-2}}{r^2 s^{-3}} \][/tex]
3. Divide the exponents:
[tex]\[ = \frac{r}{r^2} \cdot \frac{s^{-2}}{s^{-3}} = r^{-1} \cdot s^{1} \][/tex]
4. Simplify:
[tex]\[ = \left(r^{-1} s\right)^{-1} \][/tex]
5. Take the reciprocal of the simplified expression:
[tex]\[ = \frac{r}{s} \][/tex]
6. Substitute [tex]\(r = -1\)[/tex] and [tex]\(s = -2\)[/tex]:
[tex]\[ = \frac{-1}{-2} = \frac{1}{2} \][/tex]

Drake's Work:
1. Expression: [tex]\(\left(\frac{r s^{-2}}{r^2 s^{-3}}\right)^{-1}\)[/tex]
2. Substitute [tex]\(r = -1\)[/tex] and [tex]\(s = -2\)[/tex]:
[tex]\[ = \left(\frac{(-1)(-2)^{-2}}{(-1)^2(-2)^{-3}}\right)^{-1} \][/tex]
3. Simplify the exponents:
[tex]\[ = \left(\frac{(-1)(\frac{1}{4})}{(1)(-\frac{1}{8})}\right)^{-1} = \left(\frac{-1 \cdot \frac{1}{4}}{\frac{1}{-8}}\right)^{-1} \][/tex]
4. Simplify further:
[tex]\[ = \left(\frac{-\frac{1}{4}}{-\frac{1}{8}}\right)^{-1} \][/tex]
5. Evaluate the fractions:
[tex]\[ = \left(\frac{-1}{4} \cdot \frac{8}{-1}\right)^{-1} = \left(2\right)^{-1} = \frac{1}{2} \][/tex]

Therefore, both Selena and Drake, after correctly simplifying and substituting, arrived at the same result: [tex]\(\frac{1}{2}\)[/tex].

Conclusion:
Both Selena and Drake are correct in their evaluation of the expression [tex]\(\left(\frac{r s^{-2}}{r^2 s^{-3}}\right)^{-1}\)[/tex] when [tex]\(r = -1\)[/tex] and [tex]\(s = -2\)[/tex]. The final result for both of their methods is [tex]\(\frac{1}{2}\)[/tex].
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.